QUALITY IMPROVEMENT MANAGEMENT AT THE SENIOR HIGH SCHOOL MODEL IMPLEMENTING NATIONAL STANDARDIZED SCHOOL CATEGORY (SKM), LOCAL PROMINENCE BASED EDUCATION (PBKL), AND LEARNING RESOURCE CENTER (PSB) IN THE WEST NUSA TENGGARA - Furqan, Aidy; Bafadal, Ibrahim; *, Wahjoedi; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The purpose of this qualitative research is to: (1) describing the process offormulating strategic plans in the quality improvement managementin schoolmodelsimplementing National Standardized School Category (SKM), LocalProminence Based Education (PBKL) and Learning Resource Center(PSB);(2)describing the implementation of the quality improvement management inschool models implementing National Standardized School Category (SKM), LocalProminence Based Education (PBKL) and Learning Resource Center (PSB) (3)describing how to organize the quality improvement management school modelsimplementing National Standardized School Category (SKM), Local ProminenceBased Education (PBKL) and Learning Resource Center (PSB) (4) describing theevaluation system in the quality improvement management school modelsimplementing National Standardized School Category (SKM), Local ProminenceBased Education (PBKL) and Learning Resource Center (PSB). This research wasconducted by using both qualitative and quantitative approach. The data collectedusing qualitative method was aimed at providing enriched and complete information,as well as emphasizing the quantitative data. Data collection technique used interviewinstrument, field observation and documentation research. The data sources were theprincipals, the vice principals, the teachers, the high school models teams, the schoolboards and the students.